2015
DOI: 10.1111/jcpe.12369
|View full text |Cite
|
Sign up to set email alerts
|

Primary prevention of peri‐implantitis: Managing peri‐implant mucositis

Abstract: Aims: Over the past decades, the placement of dental implants has become a routine procedure in the oral rehabilitation of fully and partially edentulous patients. However, the number of patients/implants affected by peri-implant diseases is increasing. As there are -in contrast to periodontitis -at present no established and predictable concepts for the treatment of peri-implantitis, primary prevention is of key importance. The management of peri-implant mucositis is considered as a preventive measure for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
518
1
29

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 476 publications
(562 citation statements)
references
References 16 publications
14
518
1
29
Order By: Relevance
“…1 Longitudinal studies have consistently demonstrated that good standards of oral hygiene and regular maintenance reduce the incidence of caries, periodontal disease, and tooth loss, and, more recently, that they improve the outcomes of treatment with dental implants. 2,3,4,5 A classical study related to this topic was performed in Sweden; it demonstrated that a strict oral hygiene regimen reduced tooth loss, the number of new decayed surfaces, and periodontal attachment loss. 3 Other studies have also demonstrated the effects of supragingival plaque control on different oral health parameters, reinforcing its importance as the core of preventive dentistry.…”
Section: Introductionmentioning
confidence: 99%
“…1 Longitudinal studies have consistently demonstrated that good standards of oral hygiene and regular maintenance reduce the incidence of caries, periodontal disease, and tooth loss, and, more recently, that they improve the outcomes of treatment with dental implants. 2,3,4,5 A classical study related to this topic was performed in Sweden; it demonstrated that a strict oral hygiene regimen reduced tooth loss, the number of new decayed surfaces, and periodontal attachment loss. 3 Other studies have also demonstrated the effects of supragingival plaque control on different oral health parameters, reinforcing its importance as the core of preventive dentistry.…”
Section: Introductionmentioning
confidence: 99%
“…This recent paper is in contradiction with the suggestion of Jepsen et al. (2015) that mucositis is a precursor for peri‐implantitis. This contradiction does not imply that one should become negligent and should not strive for the prevention of mucositis with good oral hygiene.…”
Section: Introductionmentioning
confidence: 99%
“…A regular periodontal maintenance program is also essential. Jepsen et al 25 reported that inadequate dental biofilm control has been associated with peri-implant disease. Marron et al 7 showed that high biofilm indices (30% or more) may increase the risk of peri-implant disease compared to patients with low index biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…One should take time to ensure that oral hygiene instructions are properly passed to the patient and that they have understood the importance of effective biofilm control. 26 Thus, the patient's cooperation including biofilm control and attendance to periodontal therapy support are relevant factors to prevent the development of mucositis and periimplantitis [25][26][27] .…”
Section: Discussionmentioning
confidence: 99%